Distinct financial distress profiles in patients with breast cancer prior to and for 12 months following surgery. Issue 3 (10th September 2020) - Chan, Raymond; Cooper, Bruce; Paul, Steven; Conley, Yvette; Kober, Kord; Koczwara, Bogda; Chan, Alexandre; Tan, Chia Jie; Gordon, Louisa; Thomy, Lebogang; Levine, Jon; Miaskowski, Christine
Abstract : Background: Study purposes were to identify subgroups of patients with breast cancer with distinct self-reported financial distress (FD) profiles and determine which demographic, clinical and symptom characteristics, as well as quality of life (QOL) outcomes were associated with subgroup membership. Methods: Patients (n=391) who were assessed for changes in FD a total of 10 times from prior to through 12 months after breast cancer surgery. Latent profile analysis was used to identify subgroups of patients with distinct FD profiles. Results: Three distinct FD profiles (ie, None (14.6%), Low (52.7%), High (32.7%)) were identified. Compared with None and/or Low subgroups, patients in the High subgroup were more likely to report a lower annual household income and performance status; had a higher body mass index, axillary lymph node dissection and more advanced stage disease; had a longer time from cancer diagnosis to surgery; and had received neoadjuvant or adjuvant chemotherapy. In addition, patients in the High subgroup reported higher fatigue, sleep disturbance, state/trait anxiety, depressive symptom scores, and lower attentional function and QOL scores. Conclusion: This study provides new insights on risk factors for and evidence of a higher symptom burden associated with FD. Findings from this study provide clinicians with information on how to identify high-risk patients and to recommend appropriate interventions for both symptom management and FD. Additional research on the mechanisms that underlie the relationships among FD and common physical and psychological symptoms may inform future interventions.